2018
DOI: 10.1371/journal.pone.0197927
|View full text |Cite
|
Sign up to set email alerts
|

A survey of genetic fetal-haemoglobin modifiers in Nigerian patients with sickle cell anaemia

Abstract: Genetic variants at three quantitative trait loci (QTL) for fetal haemoglobin (HbF), BCL11A, HBS1L-MYB and the β-globin gene cluster, have attracted interest as potential targets of therapeutic strategies for HbF reactivation in sickle cell anaemia (SCA). We carried out the first systematic evaluation of critical single nucleotide polymorphisms at these disease modifier loci in Nigerian patients with SCA. Common variants for BCL11A and HBS1L-MYB were strongly associated with HbF levels. At both loci, secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
8
15
1
Order By: Relevance
“…The participants in this study showed a mean level of Hb F of 8.9 ± 6.4% which is similar to values reported by other studies on African SCA children, e.g., from Nigeria, Uganda, or Congo Republic, who presented 9.9 ± 6.0% [31], 9.0 ± 5.6% [32], and 8.8 ± 5.8% [33], respectively. Nevertheless, in other studies, lower values of Hb F have been reported for African SCA populations [34][35][36][37]. This discrepancy may be the result of several factors, such as the method used for the Hb F estimation, the age of the SCA patients, or due to environmental, cellular, and genetic factor modulators of phenotypic expression of Hb F. A level of Hb F above 10% has been suggested as necessary for reduced SCA clinical severity [30].…”
Section: Discussionmentioning
confidence: 98%
“…The participants in this study showed a mean level of Hb F of 8.9 ± 6.4% which is similar to values reported by other studies on African SCA children, e.g., from Nigeria, Uganda, or Congo Republic, who presented 9.9 ± 6.0% [31], 9.0 ± 5.6% [32], and 8.8 ± 5.8% [33], respectively. Nevertheless, in other studies, lower values of Hb F have been reported for African SCA populations [34][35][36][37]. This discrepancy may be the result of several factors, such as the method used for the Hb F estimation, the age of the SCA patients, or due to environmental, cellular, and genetic factor modulators of phenotypic expression of Hb F. A level of Hb F above 10% has been suggested as necessary for reduced SCA clinical severity [30].…”
Section: Discussionmentioning
confidence: 98%
“…The Hb F levels are much higher than those found in SCD patients of Sub-Saharan African origin, and levels greater than 20% would typically be associated with less severe clinical picture. Hb F boosting allele "C" of rs6545816 was detected at a much higher frequency in Sri Lankan patients than in patients from the United Kingdom (34%), Tanzania (36%) and Nigeria (35%) [27,28]. Furthermore, "T" allele of rs1427407 was significantly associated with high Hb F levels (p = 0.04).…”
Section: Discussionmentioning
confidence: 94%
“…The Hb F levels are much higher than those found in SCD patients of Sub-Saharan African origin, and levels greater than 20% would typically be associated with less severe clinical picture. Hb F boosting allele "C" of rs6545816 was detected at a much higher frequency in Sri Lankan patients than in patients from the United Kingdom (34%), Tanzania (36%) and Nigeria (35%) (18,37). Furthermore, among those who were not on transfusion and hydroxyurea (n=22), "T" allele of rs1427407 was signi cantly associated with high Hb F levels (p 0.046).…”
Section: Genetic Ndingsmentioning
confidence: 96%
“…One Hb F modi er (rs7482144 in Xmn1-HBG2) was genotyped by RFLP. These Hb F markers were selected based on their positive association with Hb F levels in SCD patients suggested by several studies (17)(18)(19).…”
Section: Genotyping Of Foetal Haemoglobin (Hb F) Modi Ers Among Scd Pmentioning
confidence: 99%